Development of code detector to determine E-commerce search engine quality using Website Quality Evaluation Model (OEM) / Mohd Fadhli Atan @ Tan Ah Tang - Atan @ Tan Ah Tang, Mohd Fadhli (Hospital UiTM Puncak Alam, 2006)
Search engine is a software program that searches a database and gathers and reports information that contains or is related to specified terms. Search engine is used in a website whose primary function is providing a search engine for gathering and reporting information available on the Internet or a portion of the Internet. In e-commerce website, search engine functionality is important for the customer to find the thing that they want in the website faster and easier. However, at this moment, there is no automated data collection that can detect the quality of search engine. So, in this research paper, the researcher is focus on developing a code detector to determine the quality of search engine functionality in e-commerce website refering to Website Quality Evaluation Model (QEM) by Luis Olsina Santos. The researcher scopes his study to e-commerce websites in Malaysia and also only ecommerce websites that are using PHP platform.